БОЛАЛАР СПОРТИНИ РИВОЖЛАНТИРИШНИНГ ТАШКИЛИЙ, ИЛМИЙ ВА УСЛУБИЙ АСОСЛАРИ - Қалжанов, П. (SCIENCE and SOCIETY, 2023)
The article focuses on the use of various scientific sources on physical education as an organizational, scientific and methodical basis for the development of children’s sports. It is concluded that the training is appropriate if it is organized taking into account the age, gender and physical development of the children involved in sports.